Kinerja Irigasi Bawah Permukaan Otomatis Nirdaya Pada Budidaya Kangkung, Caisim, Dan Bayam - Syafriyandi, Debby; Setiawan, Budi Indra; Arif, Chusnul; Suwardi, Suwardi (Jurnal Keteknikan Pertanian, 2023)
The automatic subsurface irrigation that was used as an object in this study is intended to provide water directly to the root zone and will stop when sufficient using a water level valve. This study aims to evaluate the performance of this irrigation model on 3 types of vegetables, namely water lettuces, choy-sum, and spinach with indicators of land productivity, water productivity, and plant coefficients. The irrigation network is a series of 12 potted plants, each measuring 33 cm in top diameter, 23.5 cm in bottom diameter, and 31 cm in height. One pot of the same size is used as a water level controller. Automatically irrigation water flows when there is a decrease in the water level in each plant pot. The set water level is 10 cm below the soil surface. The obtained results, land productivity of choy-sum is 9.6 kg m-2, spinach 3.6 kg m-2, and water lettuce 25.1 kg m-2. Water productivity choy-sum is 29.0 kg m-3, spinach 12.3 kg m-3, and water lettuce 52.4 kg m-3. The crop coefficient for choy-sum ranges from 0.12–1.71, spinach 0.12–0.94, and water-lettuce 0.16–1.46. It can be concluded that this model of unpowered automatic subsurface irrigation is very effective and efficient and easy to maintain and operate.